18F-NaF Uptake in Breast Cancer. (November 2020) - Liu, Huipan; Liu, Lin; Fu, Wenhui; Chen, Yue
Abstract : Abstract: A 55-year-old woman with back pain underwent 18 F-NaF PET/CT study to evaluate bone metastases from newly diagnosed breast cancer. Multiple foci of increased tracer uptake indicating osteoblastic metastases were noted in cervical and thoracic vertebrae. Unexpectedly, breast cancer also revealed increased NaF activity.